Preventive oral health care for mitigating the COVID-19 induced adverse maternal outcomes: View point from Sri Lanka on opportunities in crisis - Irosha Perera; Manosha Perera; Nadisha Ratnasekera; Chandana Gajanayake; Migara Epa (Journal of Gynecological Research and Obstetrics - Peertechz Publications, 2021)
Pregnancy marks a unique milestone in woman's life cycle enriched with an array of physical, psychological, social and even spiritual needs. In this context, an optimal level of oral health status has become fundamental to overall health and well-being of a pregnant woman. This is evident more than ever before, for preventing exacerbation of poor oral health in pregnancy, possible control of adverse pregnancy outcomes whilst ensuring low risk for early childhood dental caries for the offspring. Nevertheless, pregnancy renders special oral health needs for a woman compounded by changes in dietary habits, oral hygiene practices and hormonal changes thereby increasing the risk of dental caries and periodontitis. The possible link between Periodontitis and adverse outcomes in pregnancy is well known. The pandemic caused by acute respiratory syndrome coronavirus 2 (SARS-CoV-2) compounded by emergence more virulent strains not only indelibly impacted on population, countries, economies and health systems across the globe but exposed vulnerable population groups to pervasive health catastrophes. There is accumulating concerns on periodontitis linking with severe complications of Covid-19 attributed to commonalities of exacerbated inflammatory responses. Moreover, adverse Covid-19 induced maternal and fetal outcomes has garnered attention of researchers based on the previous knowledge indicating adverse outcomes attributed to epidemics of human corona viruses. However, it is not known how maternal oral hygiene status and burden of periodontitis impact on Covid-19 induced adverse outcomes in pregnancy. However, it could be rational to argue that poor oral health of a pregnant woman could elevate her risks for adverse health outcomes. Oral health care in pregnancy has received recognition as an essential element of comprehensive antenatal health care provision. However, the persistent global public health emergency of Covid-19 has profoundly impacted on availability of and accessibility to routine oral health care services. Therefore, accessing routine oral health care services poses serious causes for concern among pregnant women. Against this backdrop, present opinion attempts to explore and expound the potential of preventive oral health care could offer to mitigate the potential risks of Covid-19 induced adverse maternal outcomes embracing the context of Sri Lanka: a developing lower middle-income country.